TÜRKÇE DERS KİTAPLARINDA (1-4.SINIF) YER ALAN MASALLARIN ÖĞRETİM PROGRAMLARI VE İÇERİK AÇISINDAN İNCELENMESİ. - ÖZCAN, Derya; ŞARA, Perihan (Electronic Turkish Studies)
The main objective of this research is to study the function of the tales in Turkish Education Programme and its reflection on Turkish course books and activity books used as a training material in primary schools. Tales remain one of the most ancient popular narratives that represent folklore and culture of a society. Through these folkloric literary works brought about and carried out in oral tradition, events are given infused with extraordinary and supernatural phenomena. This state of being extraordinary and supernatural makes the listener imagine himself or herself as the protagonist of the tale and live through this world of fantasy. The use of opposite concepts such as good and bad contains some features such as rewarding the good and punishing the bad at the end of the narrative so that the reader and the listener can draw a clear moral associated with the function of the tales. In other words, the main function of this genre of narrative is to educate, so tales play a significant role in teaching and learning Turkish language. The main data source of the survey includes the Turkish Education Program, the course books and activity books that are prepared by the Turkish Ministry of Education used as education material during the 2014-2015 education semester in the 1st, 2nd, 3rd and 4th grades in primary schools. The total number of tales in the 2nd grade course books is less than those in the 3rd grade course books. Activities in activity books are by and large in keeping with the acquisitions targeted by the Turkish Education Programme. In general, tales that elaborately treat the subjects such as problem solving, paths of success, overcoming the hardship, being determined, avoiding arrogance, protecting the environment and public properties, respecting the elderly, the importance of being hardworking, being a good human, consuming healthy food, thriftiness and having a spirit of sharer can be encountered in course books.